Estudio sobre la cooperación internacional al desarrollo. Análisis de caso: Programa de articulación de redes territoriales (PNUD) - Galarza Verkovitch, Alejandro (2016)
The use of Hard Power and coercion, as means for developing a strong foreign agenda, has lost its international legitimacy fostering the implementation of Soft Power strategies, which rely on persuasion, as catalysts to shape the preferences and actions of the States. Development aid and international organizations were forged regarding co - optive principles of action.Under the light of structuralism, development aid and international organizations were created to impose, over the States of the “periphery”, the hegemonic foreign agenda. Constructivism argues that neither foreign aid nor international organizations have an intrinsic nature or goal; institutions are what the States make of them. This research will focus on the nature of international development organization under the light of: Conctructivism and Dependency Theory. The scope of this work is to answer the question: Could the international development organizations foster the economic and social welfare of the less developed States? The conclusions of the theory review will be used on the case studys of the: Programa de Articulación de Redes Territoriales (UNDP).